Evaluating the 3D cooling performances of different vegetation combinations in the urban area. Issue 3 (4th May 2022) - Tan, Xing; Liao, Jianjun; Bedra, Komi Bernard; Li, Jiayu
ABSTRACT: Vegetation has been considered as an effective strategy to combat the urban heat island effect. Most researches have focused on evaluating the cooling effect of trees in the urban thermal environment, while little attention has been paid to the cooling effect of the vegetation combinations. Moreover, most studies are focused on the horizontal cooling performance of plants, ignoring their vertical influence. Therefore, this study evaluates the 3D (horizontal and vertical) cooling performances of the three vegetation combination scenarios in the urban area using the ENVI-met model. The study indicates that the tree-grass (TG) combination has the best 3D cooling effect, followed by the tree-shrub-grass (TSG) combination, while the shrub-grass (SG) combination has the weakest 3D cooling effect. Besides, it is economical to plant TSG combinations because fewer trees are needed than planting TG combinations. Therefore, the study recommends the tree-shrub-grass combination rather than TG or SG combination in urban areas to effectively improve the thermal environment. The study also shows that the relationship between increasing tree coverage and the resulting cooling effect is not linear. The results of this study can effectively guide the design of greening strategies in urban areas to improve thermal comfort.